Heuristic algorithm for university final examination timetabling - Thian, Tze Yung (Universiti Malaysia Sarawak (UNIMAS), 2015)
This thesis proposes a heuristic algorithm for solving faculty final examination timetabling problem. There are two parts fbr the algorithm which are course grouping and timeslot allocation. In the, first part, the grouping of courses is simplified using the lecture timetable which acts as a stepping stone, for solving constraints. Hence, proceed to the second part which allocates the course examinations into available timeslots and venue that fix the required capacity. The large class allocation will be executed first to prevent insufficient of venue with large capacity then followed by small class allocation.